'Hallwachs and the negatively charged particles'—the development of education comics. (10th August 2021) - Permana, Handjoko; Purwahida, Rahmah; Muliyati, Dewi; Rahmadini, Dini; Ambarwulan, Diah; Siswoyo, S
Abstract: In the high school context, many students only solve photoelectric effect phenomena based on the equation for maximum kinetic energy and its relationship to work functions. While the story behind this phenomenon constitutes an exciting educational experience if conveyed in an attractive visual manner, many physics teachers are concerned that students will focus on the storyline rather than engaging with the formula itself. In this study, the comic titled 'Hallwachs and the Negatively Charged Particles' was presented as a continuation of Hertz's comic from previous studies, specifically as a complement to scientific explanations of the photoelectric effect phenomenon. The comic was created following the '4D' process, including the four components of define, design, develop, and disseminate. At the define stage, a storyline was generated as part of Wilhelm Hallwach's story in order to highlight how related events helped explain the photoelectric effect phenomenon. The design stage then involved the production of a visual character that was displayed as a translation from the define stage. At the develop stage, experts in media and material conducted an assessment of the results (media expert validation score of 92% and material expert validation score of 96%, with very good interpretation). At the disseminate stage, the finished comics were uploaded to the online comic platform known as Webtoon. Readers were also asked to assess the results at that time. In summary, we found that the photoelectric effect could be visually presented in the e-comic format as a pedagogical intervention for explaining related scientific concepts.